The Influence of Competency on PT Employee Performance. Bank Mandiri Micro Banking Cluster Makassar 3 - Alfina Damayanti; Ruliaty, Ruliaty; M. Hidayat (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this research is to determine the effect of competency on the performance of PT employees. Bank Mandiri Micro Banking Cluster Makassar 3. Samples were taken from PT. Bank Mandiri Micro Banking Cluster Makassar 3 had 48 respondents. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. The data sources used are primary data and secondary data. The research instrument uses a Likert scale. Data analysis using applications Statistical Package for Social Science (SPSS) version 23. Based on the research results, it is stated that competence has a positive and significant effect on employee performance at PT. Bank Mandiri Micro Banking Cluster Makassar 3.